The Effects of Work Stress, Work Motivation, and Work-Life Balance on Job Satisfaction of Gojek Drivers in Surabaya - Kharisma Erwina Putrikuri; R. Yuniardi Rusidanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effects of work stress, work motivation, and work-life balance on Gojek driver job satisfaction in Surabaya. This study uses a quantitative method with data collection through a questionnaire, which is measured using a five-point Likert scale. The population and sample in this study were 150 Gojek driver respondents in Surabaya. The sampling technique used was purposive sampling with criteria such as: (1) Drivers who have experience working as Gojek drivers for at least more than 1 year. (2) Still active as Gojek drivers until 2025. (3) Have a main job only as a Gojek driver. The data used are primary data, and the data analysis method is multiple linear regression using SPSS 30 software. The results of the study show that: (1) Work stress, work motivation, and work-life balance simultaneously have a significant effect on job satisfaction. (2) Work stress does not have a significant effect on job satisfaction. (3) Work motivation has a positive and significant effect on job satisfaction. (4) Work-life balance has a positive and significant effect on job satisfaction.